EMOTIONAL DEPENDENCE AND THE ON-AND-OFF PHENOMENON: A CASE STUDY OF EARLY ADULT COLLEGE STUDENTS' DATING RELATIONSHIPS - Lutfiah Rahmah; Mutiawati Mutiawati (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to understand emotional dependency in dating relationships and its association with the on-and-off relationship phenomenon among students of Islamic Guidance and Counseling (Bimbingan dan Penyuluhan Islam), cohort 2022. This research employs a qualitative approach with a case study design involving students who have experienced and are currently in on-and-off relationships. Data were collected through interviews, observations, and documentation. The findings indicate that partners are perceived as the primary source of emotional support, security, and a place to share problems. Strong emotional attachment makes individuals feel comfortable with their partners, but also leads to anxiety when attention or communication decreases. This condition encourages individuals to maintain the relationship despite frequent conflicts, resulting in an on-and-off relationship pattern. The study shows that emotional dependency plays a role in sustaining unstable relationship dynamics among students.